2020
DOI: 10.7554/elife.45310
|View full text |Cite
|
Sign up to set email alerts
|

A cis-carotene derived apocarotenoid regulates etioplast and chloroplast development

Abstract: Carotenoids are a core plastid component and yet their regulatory function during plastid biogenesis remains enigmatic. A unique carotenoid biosynthesis mutant, carotenoid chloroplast regulation 2 (ccr2), that has no prolamellar body (PLB) and normal PROTOCHLOROPHYLLIDE OXIDOREDUCTASE (POR) levels, was used to demonstrate a regulatory function for carotenoids and their derivatives under varied dark-light regimes. A forward genetics approach revealed how an epistatic interaction between a ζ-carotene isomerase m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 112 publications
1
48
0
Order By: Relevance
“…Surprisingly, although the carotenoid composition is severely affected in the ccr1-1 plants ( Figure 4 ), the PLB in this mutant is fully developed and regularly arranged ( Figures 5 , 7 ). It was previously established that in the ccr2 plants, the formation of PLB is completely arrested ( Park et al, 2002 ; Cazzonelli et al, 2020 ). Such fact was attributed to the accumulation of cis -carotenes – p-Lyc and pro-neurosporene in particular.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, although the carotenoid composition is severely affected in the ccr1-1 plants ( Figure 4 ), the PLB in this mutant is fully developed and regularly arranged ( Figures 5 , 7 ). It was previously established that in the ccr2 plants, the formation of PLB is completely arrested ( Park et al, 2002 ; Cazzonelli et al, 2020 ). Such fact was attributed to the accumulation of cis -carotenes – p-Lyc and pro-neurosporene in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids form another group of molecules that are highly abundant in the PLB membrane fraction. Their structural role in the PLB formation was demonstrated in the PLB-deficient ccr2 mutant, which accumulates particular poly -cis carotenoids and maintains wild type levels of LPOR and Pchlide ( Park et al, 2002 ; Cuttriss et al, 2007 ; Cazzonelli et al, 2020 ). In the ccr2 mutant, restoration of the PLB structure is possible due to further mutations in the ζ-carotene isomerase (ZISO) pointing directly to the role of the cis -carotenoid component in the PLB structure development ( Cazzonelli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants respond to light intensity, spectral quality, and photoperiod (Babla et al., 2019; Ballaré & Pierik, 2017; Cazzonelli et al., 2020; Poorter et al., 2019). At the leaf level, blue photons are used less efficiently than orange and red photons in photosynthesis (Bugbee, 2016; Inada, 1976; McCree, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specific metabolites have been identified that accumulate under stress, such as the dinucleotide 3 0 -phosphoadenosine-5 0 -phosphate (PAP) [36] and the isoprenoid precursor MEcPP [37]. Furthermore, an apocarotenoid-dependent signal was recently identified that is required for proper plastid development [39]. All these metabolites are much more stable than ROS and could be actively transported across the chloroplast envelope, diffuse through the cytosol and induce appropriate responses in the nucleus.…”
Section: (B) Operational Signalling From Plastidsmentioning
confidence: 99%